The Gibean solution (Jgs 19-21) - a mirror to reclaiming women dignity in Zimbabwe - Canisius Mwandayi; Sophia Chirongoma (HTS Teologiese Studies/Theological Studies, 2023)
Chronicling the history of gendered and sexualised violence in Zimbabwe, our article upholds the view that what transpired in Judges 19:20–48 offers the contemporary readers some important lessons that are worth pondering over. Looking through feminist hermeneutical lenses, we engage in a comparative analysis of the gender-based violations, human rights abuses, and the lack of hospitality depicted in Judges 19–21 with the lived realities of Zimbabwean women in our contemporary times. The discussion draws to a close by proffering a theology of restorative justice. It is our argument that Zimbabwe needs healing through a non-retaliative response to some wrongdoing that prioritises repairing harm and the recognition that maintaining positive relationships with fellow humans is a core human need. This is the only way forward to reclaim and restore the humanity and dignity of women exposed to diverse forms of gender-based violence in our Mother Earth.